A review of genetic resistance to endoparasites in small ruminants and an outline of ILCA's research programme in this area - Baker, R.L.; Lahlou-Kassi, A.; Rege, J.E.O.; Reynolds, L.; Tekelye Bekele; Mukasa-Mugerwa, E.; Rey, B. (Small Ruminant Collaborative Research Support Program, 1992)
The paper reviews the evidence of genetic resistance to endoparasites both within and between breeds of sheep and goats and assesses the possibilities of breeding for increased resistance. In light of this evidence, ILCA has developed a Pan-African research programme to investigate and characterise genetic resistance to endoparasites in sheep and goats. The experimental design and research protocol is briefly outlined.